Comparison of three deep eutectic solvents and 1-ethyl-3-methylimidazolium acetate in the pretreatment of lignocellulose: effect on enzyme stability, lignocellulose digestibility and one-pot hydrolysis. Issue 72 (18th July 2016) - Wahlström, Ronny; Hiltunen, Jaakko; Pitaluga de Souza Nascente Sirkka, Mariáh; Vuoti, Sauli; Kruus, Kristiina
Abstract : The use of [EMIM]AcO and three DESs was compared in lignocellulose pretreatment with focus on cellulase stability, effects on lignocellulose and enzymatic hydrolysis of pretreated lignocellulose in both buffer and in solutions of ionic liquid or DES. Abstract : Certain ionic liquids (ILs) are well-known pretreatment chemicals for lignocellulosic substrates prior to enzymatic total hydrolysis. Deep eutectic solvents (DESs) are closely related to ILs in many properties, but are easier and on occasion cheaper to synthesize and have been claimed to be less inactivating to enzymes used in the hydrolysis, and less toxic for the environment and to micro-organisms used in fermentation. The use of DESs as lignocellulose pretreatment chemicals has not been studied to a similar extent as the use of ILs. In this study, the stability of three Trichoderma reesei cellulases (the endoglucanases Cel5A and Cel7B and the cellobiohydrolase Cel7A) and one T. reesei xylanase (Xyn11) was compared in concentrated solutions (85% w/w) of three DESs (choline chloride : boric acid in molar ratio 5 : 2, choline chloride : glycerol 1 : 1 and betaine : glycerol 1 : 1) and 1-ethyl-3-methylimidazolium acetate ([EMIM]AcO), a powerful lignocellulose-dissolving IL. The pretreatment efficiency of these chemicals was further compared in a mild pretreatment (90% w/w DES or [EMIM]AcO, 80 °C, 24 h, 5% (w/w) lignocellulose consistency) of four different substrates; microcrystalline cellulose, eucalyptus dissolving pulp, shredded wheat straw and spruce saw dust. After pretreatment, the enzymatic digestibility of the pretreated substrates was evaluated in the enzymatic total hydrolysis in three different setups, including hydrolysis of the washed pretreated substrates in buffer, and of the pretreated substrates in solutions containing 30% (w/w) and 80% (w/w) of DES or [EMIM]AcO. The stability analysis identified glycerol-containing DESs to be highly stabilizing for the cellulases, but their pretreatment efficiency was limited. [EMIM]AcO had a high pretreatment efficiency, but was highly inactivating for the used cellulases. The presence of DES or [EMIM]AcO led in all cases to decreased enzymatic hydrolysis yields. Thus, good enzymatic stability in a certain DES does not directly implicate good performance in the hydrolysis of solid lignocellulosic substrates in that DES.